High-resolution mucociliary transport measurement in live excised large animal trachea using synchrotron X-ray imaging - Martin Donnelley; Kaye S. Morgan; Maged Awadalla; Nigel R. Farrow; Chris Hall; David W. Parsons (Respiratory Research, 2017)
Abstract Background The Australian Synchrotron Imaging and Medical Beamline (IMBL) was designed as the world’s widest synchrotron X-ray beam, enabling both clinical imaging and therapeutic applications for humans as well as the imaging of large animal models. Our group is developing methods for imaging the airways of newly developed CF animal models that display human-like lung disease, such as the CF pig, and we expect that the IMBL can be utilised to image airways in animals of this size. Methods This study utilised samples of excised tracheal tissue to assess the feasibility, logistics and protocols required for airway imaging in large animal models such as pigs and sheep at the IMBL. We designed an image processing algorithm to automatically track and quantify the tracheal mucociliary transport (MCT) behaviour of 103 μm diameter high refractive index (HRI) glass bead marker particles deposited onto the surface of freshly-excised normal sheep and pig tracheae, and assessed the effects of airway rehydrating aerosols. Results We successfully accessed and used scavenged tracheal tissue, identified the minimum bead size that is visible using our chosen imaging setup, verified that MCT could be visualised, and that our automated tracking algorithm could quantify particle motion. The imaging sequences show particles propelled by cilia, against gravity, up the airway surface, within a well-defined range of clearance speeds and with examples of ‘clumping’ behaviour that is consistent with the in vivo capture and mucus-driven transport of particles. Conclusion This study demonstrated that the wide beam at the IMBL is suitable for imaging MCT in ex vivo tissue samples. We are now transitioning to in vivo imaging of MCT in live pigs, utilising higher X-ray energies and shorter exposures to minimise motion blur.